Fertility preservation, contraception and menopause hormone therapy in women treated for rare ovarian tumours: guidelines from the French national network dedicated to rare gynaecological cancers. (July 2019) - Rousset-Jablonski, Christine; Selle, Fréderic; Adda-Herzog, Elodie; Planchamp, François; Selleret, Lise; Pomel, Christophe; Daraï, Emile; Chabbert-Buffet, Nathalie; Pautier, Patricia; Trémollières, Florence; Guyon, Frederic; Rouzier, Roman; et al.
Abstract: Introduction: Rare ovarian tumours include complex borderline ovarian tumours, sex-cord tumours, germ cell tumours and rare epithelial tumours. Indications and modalities of fertility preservation (FP), infertility management, contraindications for hormonal contraception or menopause hormone therapy are frequent issues in clinical practice. A panel of experts from the French national network dedicated to rare gynaecological cancers, and experts in reproductive medicine and gynaecology have built guidelines on FP, contraception and menopause hormone therapy in women treated for ovarian rare tumours. Material and methods: A panel of 35 experts from different specialties contributed to the preparation of the guidelines, following the DELPHI method (formal consensus method). Statements were drafted after a systematic literature review and then rated through two successive rounds. Results: Thirty-five recommendations were identified, concerning indications for FP, contraindications for ovarian stimulation, contraceptive options and menopause hormone therapy for each tumour type. Discussion: Overall, caution has been recommended in the case of potentially hormone-sensitive tumours such as sex-cord tumours, serous and endometrioid low-grade adenocarcinomas, as well as for high-risk serous borderline ovarian tumours. Conclusion: In the context of a scarce literature, a formal consensus method allowed the elaboration of guidelines, which will help clinicians in the management of these patients. Highlights: Fertility preservation should be considered before any treatment. Hormonal treatments and ovarian stimulation are contraindicated in some situations. Caution is recommended in the case of potentially hormone-sensitive tumours. Caution is recommended in the case of high-risk serous borderline ovarian tumours.